POTASSIUM ADSORPTION IN CALCAREOUS SOILS OF KURDISTAN REGION OF IRAQ - Mam-Rasul, Gh. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Sorption is one of the most chemical important processes, which determine nutrients availability in soil. Sorption isotherms provide sufficient information about soils sorption’s capacity, and it’s data can be used to determine thermodynamic sorption parameters. The aim of this studyis to evaluate the sorption of potassium onto some soils. An experiment was conducted with four calcareous soils of the Sulaimani province Kurdistan Region of Iraq by using the batch methods. 5g soil samples were equilibrated at 298±1 Kelvin with 50 ml of 0.01M CaCl2 containing 0 to 250 mg L-1 K as KCl. Suspensions were centrifuged, filtered, and concentration of K+ in the clear extract solution was determined. Amount of K+ sorbed by the soil was calculated from the difference between the initial and final concentration of K+ in the equilibrium solution. Sorption of K+ was evaluated using adsorption isotherms. The results showed that K+ sorption was described by linear, Langmuir, Freundlich, and Temkin equations. Langmuir equation gave a better fit of equilibrium K adsorption when it has a higher R2 and lowers SE. The data indicated that the maximum monolayer coverage capacity (b) from the Langmuir isotherm model ranged between (-113.63 to 2500) mg kg-1. The negative values of (b) for studied locations soils indicated to potassium release instead of adsorption. The Langmuir isotherm constant (KL) ranged from (-0.01 to 0.01) L mg-1. Maximum buffering capacity (MBC) is a capacity factor, which measures the ability of the soil to replenish K ion to soil solution that the ability of a soil to supply K to the soil solution. The value of MBC of the studied soils ranged from 0.453 to 23.75 mg kg-1.The sorption processes for the forth locations are favorable and spontaneous because the value of RL was an equal one.